Method for Determination of Trace Nickel(II) with Ethylhexyl Benzoxazole Sulphide - Dong, Xiangyun; Huang, Zhangjie; Feng, Shaoping (Asian Journal of Chemistry, 2010)
Synthesis and application of ethylhexyl benzoxazole sulphide (EHBS), as a new chromogenic reagent for the determination of nickel has been described. Highly sensitive, selective and fast method for determination of nickel based on its rapid reaction with ethylhexyl benzoxazole sulphide and the solid phase extraction of the coloured complex on a nonpolar resin DIAION HP20 has been developed. In the presence of pH 4.7 acetic acid-sodium acetate buffer solution and sodium dodecyl sulfate (SDS) medium, ethylhexyl benzoxazole sulphide reacted with nickel to form coloured complex of nickel-to-EHBS molar ratio of 1:2. The complex was enriched by the solid phase extraction with the DIAION HP20 cartridge. The complex was eluted from the cartridge with dimethyl formamide (DMF) and enrichment factor of 100 was achieved. In DMF medium, molar absorptivity of the complex was 1.03 × 105 L mol-1 cm-1 at 600 nm. Beer's law was obeyed in the concentration range 0.01-0.7 μg mL-1. The relative standard deviation for eleven replicate samples at the 0.6 μg L-1 level was 2.8 %. In the original sample detection limit was 0.08 μg L-1. This method was applied to the determination of trace nickel in water samples with good result.